CRITICAL ANALYSIS OF THE BNCC: POSITIVE AND NEGATIVE ASPECTS (REMUNOM, 2025)
The National Common Curricular Base is the guiding document for Brazilian Basic Education. This document has been criticized and defended by various sides; this article presents reflections on this subject. Its objective is to analyze the positive and negative aspects of the BNCC according to the views of some authors. To this end, a bibliographic research of the narrative review type was developed through the study of scientific articles. The analysis of the studied data followed the analysis of free interpretation, that is, it was carried out in a reflective, open and subjective manner, according to the understanding and interpretation of the authors in relation to the texts studied. As a result, it is evident that the BNCC aims to standardize basic education in Brazil, ensuring that all students develop essential skills for the full exercise of citizenship. Its positive points include the search for greater educational equity, the comprehensive education of students and a flexible and interdisciplinary curriculum. However, criticism points out that its focus on skills aimed at the job market can weaken critical and reflective training, reflecting a neoliberal agenda. The emphasis on utilitarian skills could limit students' autonomy and reflection on social and political issues.